Reconciliation or Racialization? Contemporary Discourses about Residential Schools in the Canadian Prairies - Gebhard, Amanda M (Canadian Journal of Education/Revue canadienne de l’éducation, 2017)
The residential school system is one of the darkest examples of Canada’s colonial policy. Education about the residential schools is believed to be the path to reconciliation; that is, the restoration of equality between Aboriginal and non-Aboriginal peoples in Canada. While the acquisition of the long-ignored history of residential schools has the potential to centre marginalized perspectives and narratives, knowledge acquisition alone is not necessarily a reconciliatory endeavour. The critical discourse analysis offered in this article reveals how dominant narratives about residential schools, cited by well-meaning educators, re-inscribe harmful colonial subjectivities about Aboriginal peoples. Through a post-structural lens and drawing from interviews conducted across one prairie province, I demonstrate how citing popular, contemporary discourses about residential schools continues to racialize Aboriginal peoples while positioning non-Aboriginal peoples as supportive and historically conscious. Readers are brought to think about how learning about residential schools for reconciliation might be approached as the disruption of subjectivities and the refusal to (re)pathologize Aboriginal peoples. Otherwise, efforts at reconciliation risk re-inscribing the racism that justified residential schools in their inception.